الكسور المفصلية المفتتة للنهاية البعيدة للكعبرة عند البالغين - يوسف صفوان; سعد معن; جمعة جمال (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 47 مريضا", منهم 22 ذكرا"(46.8 % ) و 25 أنثى (53.2 %). 34 % من المرضى هم من الرجال دون 50 عاما" و 44.8 % من المرضى هم من النساء فوق 50 عاما". عولج 31 مريضا"علاجا" محافظا", منهم 10مرضى(29%) حدثت لديهم اختلاطات ( ألم أو تحدد حركة) . عولج7 مرضى بالصفيحة الراحية ,حدث تحدد حركة معتدل لمريض واحد وضمورسوديك تراجع لدى مريض آخر. عولج 9 مرضى بالتثبيت الخارجي( AO ومتعدد المستويات) وصفيحة الشد ( [1,6] ( distraction plate ( الرد الرباطي ), حصل لمريضين تحدد حركة بدرجات خفيفة دون وجود أي ألم مرافق . We have studied 47 patients "22 males" (46.8%) and 25 females (53.2%),34% of patients were men under 50 and 44.8 of the patients were women over 50 years. We treated 31 patients by conservative treatment, 10 of them (29%) happened to have complications (pain or loss of movement). We have treated 7 patients by reconstruction plate, 2 of them happened to have complications ( sudik dystrophy , moderate loss of movement ). We treated 9 patients by with external fixation and distraction plate (ligamentotaxis), 2 of them happened to have complications (slight loos of movement without any pain).